Melanoma of the penis: A case diagnosed at the Anatomic Pathology Laboratory of the Treichville Teaching Hospital - Mohamed Kouyaté; Ahoua François D'horpock; N'guiessan Alphonse Aman; Zié Cheick Traore; Zana Ismael Coulibaly; Baumaney Sylvanus Koui; Kouakou Donatien Koffi; Kouakou Emmanuel Koffi (Elsevier, 2018)
Melanoma of the penis is an uncommon and unfavorable malignant tumor which is diagnosed late due to the psychological impact. We report a case of advanced melanoma of the glans penis in a 30-year-old patient. Keywords: Melanoma, Penis, Metastasis